The relationship between glomerular filtration rate, nutrition and activities of daily living in patients with chronic kidney disease receiving homecare - Ozturk, Guzin Zeren; Toprak, Dilek (Progress in Nutrition, 2019)
Introduction: The aim of this research was to evaluate the relationship among glomerular filtration rate, nutrition and activities of daily living performance in Chronic Kidney Disease patients receiving homecare services. Materials and Method: We conducted a retrospective examination of the Sisli Hamidiye Etfal Training and Research Hospital’s Homecare records for 2016. 345 patients were included. Glomerular filtration ratewas calculated using a simplified version of the Modification of Diet in Renal Disease. Mini-Nutritional Assessmen scores were used for nutrition. Barthel Index scores were used to identify activities of daily living. P values of ≤0.05 were considered statistically significant. Results: 225 women (65.2%) and 120 men (34.8%), were included. Mean value ofGlomerular filtration rate was 60.83 ± 17.10 ml/min/1.73 m2. Mini-Nutritional Assessmen test mean was 19.66 ± 4.97. Barthel Index of the study group was 30.39 ± 28.99. A statistically significant correlation was found between glomerular filtration rateand the Barthel Index(p = 0.022). When glomerular filtration ratedecreased, Barthel Index scores decreased. As Mini-Nutritional Assessmen scores decreased, glomerular filtration rate values also decreased (p = 0.029). Barthel Index and Mini-Nutritional Assessmen were also related (p = <0.001). Conclusion: In primary care, elderly individuals (especially those receiving homecare services) should undergo assessment of activities of daily living and nutritional status. Patients with Chronic Kidney Disease were at risk for malnutrition and dependence on activities of daily living.